Effect of platelet mediator concentrate (PMC) on Achilles tenocytes: an in vitro study. Issue 1 (December 2016) - Arslan, Esra; Nellesen, Thomas; Bayer, Andreas; Prescher, Andreas; Lippross, Sebastian; Nebelung, Sven; Jahr, Holger; Jaeger, Christine; Huebner, Wolf; Fischer, Horst; Stoffel, Marcus; Shakibaei, Mehdi; et al.
Abstract Background Although there are many studies discussing the etiological and pathological factors leading to both, acute and chronic tendon injuries, the pathophysiology of tendon injuries is still not clearly understood. Although most lesions are uncomplicated, treatment is long and unsatisfactory due to the poor vascularity of tendon tissue. Platelet mediator concentrate (PMC) contains many growth factors derived from platelets, which can promote wound healing. In this study we investigate the effects of PMC on tenocyte proliferation and differentiation in order to provide an experimental basis for tissue regeneration strategies and to develop new treatment concepts. Methods Using enzyme linked immunosorbent assay (ELISA) we were able to quantify the several growth factors and cytokines found in PMC. Tenocytes were isolated both from human and from mouse Achilles tendons and stimulated with PMC. CyQuant® and Cell Titer Blue® assays were carried out to analyze tendon growth and viability at different concentrations of PMC. Real time RT-PCR was used to analyze tenocyte gene expression with or without PMC treatment. Immunohistochemistry was carried out to detect the tenocyte-specific antibody tenomodulin (TNMD) and scleraxis (SCX). Results We were able to detect numerous mediators such as platelet derived growth factor BB (PDGF-BB), interleukin 6 (IL-6), vascular endothelial growth factor (VEGF), tumor necrosis factor (TNF-α), transforming growth factor beta 1 (TGF-ß1), and bone morphogenetic proteins 2, 4 and 7 (BMP-4, BMP-2, BMP-7) in PMC. It was possible to show a positive effect of PMC on human tendon cell growth and viability in a dose-dependent manner. Furthermore, PMC treatment led to induction of gene expression of scleraxis (SCX), type I collagen A 1 (Col1A1) and TNMD by tenocytes. Conclusions We suggest that the use of autologous PMC may be a suitable addition to conventional tendon therapy that is capable of increasing and optimizing tendon healing and reducing the risk of recurrence.